2006
DOI: 10.1295/polymj.38.484
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Polymerization of 6-(N-Allyl-1,1,2,2-tetrahydroperfluorodecyl)amino-1,3,5-triazine-2,4-dithiol Monosodium on Aluminum

Abstract: ABSTRACT:Polymer thin films are prepared by electrochemical polymerization of 6-(N-allyl-1,1,2,2-tetrahydroperfluorodecyl)amino-1,3,5-triazine-2,4-dithiol monosodium on an aluminum plate. The steric and chemical structures of films are characterized by optical ellipsometry, contact angle goniometry, Fourier transform infrared spectroscopy (FT-IR) and impedance spectroscopy. Polymer film thickness and potential applied to the films during electrochemical polymerization, a measure of packing density, increase pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Therefore, electropolymerization has become the mainstream technology for fabricating nanofilms of triazinedithiols. Triazinedithiol molecules with allyl and fluoro alkyl groups in their structure have been studied for many years, because these polymeric nanofilms have notable lubricity [ 6 ], high dielectric [ 11 , 12 ] and hydrophobic properties [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, electropolymerization has become the mainstream technology for fabricating nanofilms of triazinedithiols. Triazinedithiol molecules with allyl and fluoro alkyl groups in their structure have been studied for many years, because these polymeric nanofilms have notable lubricity [ 6 ], high dielectric [ 11 , 12 ] and hydrophobic properties [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 4e, two S 2p peaks appear at 162.7 eV and 163.9 eV due to the formation of S*-Mo and C-S*-C groups, respectively, 58 indicating incorporation of POT into MoS2, and another peak found at 169.2 eV is associated with the S in sulfone. Furthermore, the S peaks were observed to shift towards higher energies of 1.6 eV and 1.2 eV due to the ISM coating on POT-MoS2 film (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the most synthesized compounds are the nitrogen heterocyclic compounds. Mori studied the corrosion protection properties of triazinedithiols on the various metal substrates by adsorption and electrochemical polymerization [13][14][15]. The experiments showed that polymeric nanofilms prepared by different triazinedithiols had a basic anticorrosion property.…”
Section: Introductionmentioning
confidence: 99%